Предмет: Алгебра,
автор: jekafrolin0000
упростите выражение a)(x+1)(x^2-x+1)-(x^2-1)x b) (a^3-b^3)(a^3+b^3)+(a^2+b^2)(a^4-a^2b^2+b^4)
Ответы
Автор ответа:
0
a) (x+1)(x²-x+1)-(x²-1)x=x³+1-x³+x=x+1
b) (a³-b³)(a³+b³)+(a²+b²)(a⁴-a²b²+b⁴)=a⁶-b⁶+a⁶+b⁶=2a⁶
b) (a³-b³)(a³+b³)+(a²+b²)(a⁴-a²b²+b⁴)=a⁶-b⁶+a⁶+b⁶=2a⁶
Автор ответа:
0
спасибо!)
Автор ответа:
0
в а.) ошибочка небольшая
Автор ответа:
0
x³+1-x³+Х=х+1
Автор ответа:
0
спасибо, исправлено
Автор ответа:
0
а.)
(x+1)(x^2-x+1)-(x^2-1)x=(x+1)(x^2-x+1)-(x-1)(х+1)x=(х+1)(( x^2-x+1)-х(х-1))= (х+1)( x^2-x+1-х^2+х)=х+1
(x+1)(x^2-x+1)-(x^2-1)x=(x+1)(x^2-x+1)-(x-1)(х+1)x=(х+1)(( x^2-x+1)-х(х-1))= (х+1)( x^2-x+1-х^2+х)=х+1
Похожие вопросы
Предмет: Қазақ тiлi,
автор: Аноним
Предмет: Английский язык,
автор: 67693
Предмет: Алгебра,
автор: sulpak02062015aliy
Предмет: Математика,
автор: Tanya12976
Предмет: Алгебра,
автор: dosik2000